A Critical Review on Clinical Manifestations of Obesity in Type 2 Diabetes Mellitus and Solution through Physical Activity - Charu Bansal; Rachna Jain; Umesh Shukla; Smita Paul (International Journal of Ayurveda and Pharma Research, 2021)
Diabesity term recently coined in medical field because of the very close epidemiological and pathogenic associations between central obesity and Type 2DM. Material and Methods: This review is based on data collected from published research works in various journals. Observations and Results: cited based on research reviews to find out risk odds of obesity and physical inactivity and initiation of type 2 diabetes with solutions based on improve physical activity. Conclusion: Counseling would be one of the best strategies to opt physical exercise with moderate and vigorous intensity recommended as world health organization as healthy behaviour to prevent and control of type 2 diabetes. Thus, Present write up is an effort to critically evaluate and assess the published research data on obesity and its association with development of type 2 diabetes and role of Physical exercises for prevention and control of type 2 DM as its solution with research evidences.